(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research is motivated by the importance of character education for muallaf students in the process of adjusting to Islamic values after embracing Islam. This study aims to describe the process of character transformation of muallaf students and to analyze the factors that support the formation of character in the Two-Year Religious Education Program at PETAMA Pahang, Malaysia. The research uses a qualitative approach with a phenomenological type to deeply understand the life experiences of muallaf students. Research subjects were selected using purposive sampling techniques with the criteria of muallaf students who had participated in the education program for at least one year. Data were collected through in-depth interviews, observation, and documentation. Data were analyzed using thematic analysis through the process of data reduction, coding, theme grouping, data presentation, and conclusion drawing. The results of the study indicate that the transformation of the adab of muallaf students occurs gradually through religious learning, worship habituation, teacher role models, a religious environment, and peer support. The humanistic approach of educators and the internal motivation of students are the main factors in the success of adab guidance. This study concludes that systematic, humanistic, and habituation-based religious education can shape changes in religious behavior, worship discipline, and the Islamic identity of muallaf students more profoundly and sustainably.